2022
DOI: 10.3390/land11081147
|View full text |Cite
|
Sign up to set email alerts
|

China’s Transport Land: Spatiotemporal Expansion Characteristics and Driving Mechanism

Abstract: The literature about changes in land use includes many studies of global sustainable development goals, while studies of transport land expansion have been relatively scarce. In this paper, we present an analysis of the spatiotemporal characteristics of transport land expansion in China’s 31 provinces from 2009 to 2017, applying the spatial Dubin model to identify the factors that influenced changes in per capita transport land area (PCTLA). The eastern and western regions have continued to lead the nation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 52 publications
0
1
0
Order By: Relevance
“…The decision-making of stakeholders is closely linked to the process and dynamic change of land use. Previous research on land-use structure adjustment primarily regarded the government or its policies as one of the influencing factors, considering local government decision-making as only a part of the outcomes of land-use adjustment [40,41]. Consequently, this study aims to address this gap by examining land use from the perspective of the local government as a stakeholder, providing a more comprehensive understanding of the influencing factors, decisions, and objectives of the local government in land-use structure adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…The decision-making of stakeholders is closely linked to the process and dynamic change of land use. Previous research on land-use structure adjustment primarily regarded the government or its policies as one of the influencing factors, considering local government decision-making as only a part of the outcomes of land-use adjustment [40,41]. Consequently, this study aims to address this gap by examining land use from the perspective of the local government as a stakeholder, providing a more comprehensive understanding of the influencing factors, decisions, and objectives of the local government in land-use structure adjustment.…”
Section: Discussionmentioning
confidence: 99%
“…The third quadrant is the low–low (LL) agglomeration area, indicating that the province with a low ULGUE value is surrounded by other provinces with low ULGUE values. The fourth quadrant is the high–low (HL) agglomeration area, which implies that a province has a high ULGUE value, but is surrounded by provinces with low ULGUE values [ 42 , 43 ].…”
Section: Methodsmentioning
confidence: 99%
“…This study considers the factors affecting transportation land demand identified in previous research and refines and synthesizes these factors through meta-analysis. Compared to existing studies, the framework of influencing factors developed in this study is more applicable and comprehensive [5]. Furthermore, the model constructed in this study incorporates the constraints of future socio-economic development objectives, ensuring that the forecasted area of land for transportation aligns with future socio-economic goals and is deemed reasonable.…”
Section: Implications and Applicationsmentioning
confidence: 99%
“…In terms of land area requirements for transportation infrastructure, roads, railways, and parking facilities are estimated to encompass an area of 250,000 to 350,000 square kilometers by 2050, which is approximately equivalent to the size of the UK and Germany, respectively [4]. Over the past decade, China has experienced rapid development in its transportation sector, accompanied by a substantial expansion in the land area allocated for transportation [5]. Since 2015, the area allocated to transportation land in China has surpassed all other types of construction land.…”
Section: Introductionmentioning
confidence: 99%